Pengaruh Kepemilikan Institusional, Pertumbuhan Penjualan dan Nilai Perusahaan terhadap Agresivitas Pajak - Muhammad Eko Ari Wibowo; Chaeru Syahru Ramdani; Adi Sofyana Latif; Rananda Septanta (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Tax aggressiveness remains an important issue in corporate financial management, particularly in consumer non-cyclical companies that tend to maintain stable performance across economic conditions. Differences in ownership structure and financial performance may influence managerial decisions related to tax planning. This study aims to analyze the effect of institutional ownership, sales growth, and firm value on tax aggressiveness in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. This research employs a quantitative approach with an associative research design. The sample was selected using purposive sampling, resulting in 15 companies with a total of 75 financial statement observations. The data were processed using Eviews 12 and analyzed through panel data regression techniques. The results indicate that, partially, institutional ownership has no significant effect on tax aggressiveness, suggesting that institutional investors may not effectively restrain corporate tax-related decisions. In contrast, sales growth and firm value have a significant effect on tax aggressiveness, indicating that companies with higher sales growth and greater market value tend to engage more aggressively in tax planning to maximize profits. Simultaneously, institutional ownership, sales growth, and firm value jointly affect tax aggressiveness. These findings imply that tax supervision and policy formulation should consider firm performance and market value characteristics in addition to ownership structure when addressing corporate tax aggressiveness.